Quality Standards in the learning Environment Through the Internet at Higher Education - Mahmood Abdulsalam Al-Hafedh (University of Science and Technology, Yemen, 2004)
Quality Standards in the learning Environment Through the Internet at Higher Education Abstract:    The aim of this study is to determine the Standards of applying an Online Learning environment in higher education institutions, through the analysis of the literatures, and the appropriate previous studies. The researcher has identified a list of Standards that should be available to determine whether the higher education institutions have the ability to provide opportunities for the application of Online Learning. Eight criteria have been identified for this purpose with a set of indicators associated with each Standard to govern it. The eight Standards are the Quality in the aims Online Learning, the Physical elements, software and human resources to online Learning, the tools of Online Learning, the design of teaching materials for online Learning, the training and qualifying of University lecturer, the Guidance and tutoring for Online Learning students, the social and cultural relations for Online Learning and the physical environment for Online Learning.    The researcher recommended dependence on the list of standards that have been reached in order to achieve quality in the application of Online Learning Environment. The researcher suggests a study of Online Learning universities is evaluated in the light of the application of quality standards Online Learning, and to conduct studies on the design of Online Learning Environments in the light of quality standards. Key words: (E-Learning, Online Learning , Online Learning  Environment, quality standards)